Visible‐Light‐Accelerated Copper(II)‐Catalyzed Regio‐ and Chemoselective Oxo‐Azidation of Vinyl Arenes. Issue 27 (1st June 2018) - Hossain, Asik; Vidyasagar, Adiyala; Eichinger, Christian; Lankes, Christian; Phan, Jenny; Rehbein, Julia; Reiser, Oliver
Abstract: The visible‐light‐accelerated oxo‐azidation of vinyl arenes with trimethylsilylazide and molecular oxygen as stoichiometric oxidant was achieved. In contrast to photocatalysts based on iridium, ruthenium, or organic dyes, [Cu(dap)2 ]Cl or [Cu(dap)Cl2 ] were found to be unique for this transformation, which is attributed to their ability to interact with the substrates through ligand exchange and rebound mechanisms. Cu II is proposed as the catalytically active species, which upon coordinating azide will undergo light‐accelerated homolysis to form Cu I and azide radicals. This activation principle (Cu II ‐X→Cu I +X . ) opens up new avenues for copper‐based photocatalysis. Abstract : Photocatalytic oxo‐azidation of vinyl arenes with trimethylsilylazide and O2 as stoichiometric oxidants was achieved in the presence of [Cu(dap)2 ]Cl or [Cu(dap)Cl2 ]. Cu II is proposed as the catalytically active species, which upon coordinating azide will undergo light‐accelerated homolysis to form Cu I and azide radicals. This activation principle (Cu II ‐X→Cu I +X . ) opens up new avenues for copper‐based photocatalysis. dap=2, 9‐Bis( p ‐anisyl)‐1, 10‐phenanthrolin.